ROSCOU POUND: HUKUM SEBAGAI ALAT REKAYASA SOSIAL (KETERHUBUNGANNYA DENGAN KAIDAH LA YUNKARU TAGAYYUR AL-AHKAM BI TAGAYYURI AZZAMAN) - Yahya, M. Yusuf; Alimuddin, Harwis (Indonesian Journal of Shariah and Justice, 2022)
This study aims to reveal the relationship between Roscou Pound's thoughts and the rule of la yunkaru tagayyur al-ahkam bi tagayyuri azzaman. This study uses a qualitative approach in explaining, describing, and analyzing in-depth the research results. The data collection technique used is a literature study. This study concludes that the Roscue Pound theory; law is a tool of social engineering, contributes that the law is not imperative to society. Law is seen as having a role to change human behavior in accordance with the circumstances, and socio-cultural, dynamics of society. The law is not seen as a rigid, elastic law, this is also an emphasis on the rule of la but yunkaru taghayyur al-ahkam bi taghayyuri azzaman. Roscue Pound's theory also, Sociological Jurisprudence, has the same direction, that society has individual and collective roles in the implementation of applicable law. Positive law will only be effective if it is in harmony with the laws that live in society. Like Roscue Pound's theory, the theory in fiqh rules also opens up legal changes in society on the basis of differences in culture, different habits and customs.